ANALYSIS INFLUENCE INSTRUMENT POLICY MACROPRUDENTIAL TO COMMERCIAL BANK LIQUIDITY IN INDONESIA IN THE 2018 PERIOD - Budiastuti, Maulidina Nur; Wiralaga, Harya Kuncara; Zahra, Siti Fatimah (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2022)
Liquidity is an important aspect that can be considered a bank's lifeblood. To maintain business continuity, banks must always manage liquidity effectively. Liquidity easing is one strategy to assist economic growth during the COVID-19 epidemic. Where macroprudential policies are used to ease liquidity restrictions. As a means of promoting economic growth, the government seeks to induce greater lending to debtors. This easing of liquidity, on the other hand, is thought to help maintain bank operations solvent. This easing of liquidity during the pandemic was carried out by reducing the reserve requirement followed by an increase in the MPLB ratio. In addition, Bank Indonesia strengthened RIM by adding an export money order in its calculations. The goal of this research is to look at how macroprudential policy, such as the Statutory Reserves instrument, the Macroprudential Intermediation Ratio, and the Macroprudential Liquidity Buffer, affects the liquidity of traditional commercial banks in Indonesia from 2018 to 2021. The monthly data utilized comes from the Financial Services Authority website, specifically the Indonesian Banking Statistics section. To evaluate the three hypotheses, the researchers employed a multiple linear regression approach utilizing EViews 10 software. First, the Statutory Reserves have a negative and minor influence on commercial bank liquidity, according to the findings. Second, RIM has a good and considerable impact on commercial bank liquidity. Third, PLM has a considerable negative impact on commercial bank liquidity. Simultaneously, the three independentfactors are discovered to have an impact on commercial bank liquidity.